THE RELATIONSHIP BETWEEN SELF DISCLOSURE AND RESILIENCE AMONG NURSES AT ACEH MENTAL HOSPITAL, INDONESIA: A CROSS-SECTIONAL STUDY - Zahrina, Nazila; Mawarpury, Marty; Aprilia, Eka Dian; Sulistyani, Arum (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: Registered nurses employed in acute and semi-acute wards of mental hospitals frequently encounter elevated levels of stress, a significant component of which is the constant threat of violence from patients. Consequently, the capacity to adapt in challenging circumstances is referred to as resilience. Resilience, defined as the ability to cope with adversity, enables individuals to perceive challenges as catalysts for personal growth. Purpose: to identify the relationship between self-disclosure and the level of resilience exhibited by nurses at Aceh Mental Hospital. Methods: used a quantitative correlational approach, involved 45 nurses through a total sampling technique. The instruments used were the Resilience Scale for Nurse (RSN) (α = 0.830) and the Revised Self Disclosure Scale (RSDS) consisting of five dimensions with varying reliability. Results: A substantial relationship was identified between resilience and the dimensions of intent to disclose (p=0.002; r=0.456), amount of disclosure (p=0.029; r=0.326), and positive factor of disclosure (p=0.029; r=0.326). Meanwhile, the dimensions of honesty-accuracy and control of general depth did not show a significant relationship. Conclusion: Several factors related to self-disclosure have been shown to be positively associated with resilience, suggesting that openness may play a crucial role in enhancing the mental resilience of nurses working in high-risk environments. Abstrak Latar Belakang: Perawat yang bekerja di bangsal akut dan semi-akut Rumah Sakit Jiwa kerap menghadapi tekanan berat, termasuk risiko kekerasan dari pasien. Oleh karena itu, dibutuhkan kemampuan untuk beradaptasi dan tetap tangguh dalam situasi menantang, yang dikenal sebagai resiliensi. Resiliensi memungkinkan individu untuk melihat tekanan dan kesulitan sebagai peluang untuk berkembang. Tujuan: bertujuan untuk mengidentifikasi hubungan antara self disclosure dengan tingkat resiliensi pada perawat di Rumah Sakit Jiwa Aceh. Metode: Menggunakan pendekatan kuantitatif korelasional, melibatkan 45 perawat melalui teknik total sampling. Instrumen yang digunakan adalah Resilience Scale for Nurse (RSN) (α = 0.830) dan Revised Self Disclosure Scale (RSDS) yang terdiri dari lima dimensi dengan reliabilitas bervariasi. Hasil: Terdapat hubungan signifikan antara resiliensi dengan dimensi intent to disclose (p=0.002; r=0.456), amount of disclosure (p=0.029; r=0.326), dan positive factor of disclosure (p=0.029; r=0.326). Sementara itu, dimensi honesty-accuracy dan control of general depth tidak menunjukkan hubungan signifikan. Kesimpulan: Beberapa aspek self disclosure berkorelasi positif dengan resiliensi, menunjukkan pentingnya keterbukaan dalam memperkuat daya tahan mental perawat di lingkungan kerja berisiko tinggi.